MEMBANGUN POLA KOMUNIKASI DAN PENDIDIKAN POLITIK BAGI KALANGAN GEN Z DI SMKN 1 BLADO BATANG - Setiawan, Hendy; Choirunnisa, Choirunnisa; Sutinnarto, Sutinnarto; Irawan, Rizky Rahmanda (Universitas Sanata Dharma, 2024)
The purpose of this article is to explain the importance of communication literacy and political education, especially for Gen Z. Especially in the conditions of the political year, communication literacy and political education are guidelines for Gen Z so that they can respond more rationally to their political year. This is important because many Gen Z people are not politically literate, so sometimes political frenzy can expose them to criminal charges. For this reason, communication literacy and political education are important to equip them so they can continue to exist in the political year. This service method uses an active participation approach where this program involves students at SMKN 1 Blado. In its implementation, service members carry out initial observations, location determination, implementation, evaluation, and follow-up of the service program. The results of the service program show that students are very enthusiastic and interested in the political education material presented. They feel that they are still very unfamiliar with politics, so this service program is a source of knowledge for them. Moreover, Gen Z needs literacy. Apart from that, they were also very active in discussing questions and answers, especially how Gen Z behaves politically and rationally in determining their political choices to produce optimal impacts for them.